The Significance of EU Criminal Law in the 21st Century: The Need for Further Harmonisation or New Criminal Policy? - Ragaišytė, Ieva-Marija; Švedas , Gintaras (Vilnius University Open Series, 2021)
This publication contains the proceedings of the 9th European Criminal Law Academic Network (ECLAN) PhD Seminar on European Criminal Justice "The significance of EU criminal law in the 21st century: the need for further harmonisation or new criminal policy", hosted by the Vilnius University Faculty of Law. Participants of the event presented their research in various criminal law fields related to the EU substantive criminal law and its national implementation, combating organised crime and the EPPO, criminal policy and human rights and cooperation in criminal matters and other legal instruments. Thus, the publication provides short papers of the main ideas and conclusions of several speakers’ presentations.